Manipulation of carbon assimilation with respect to expression of the pac gene for improving production of penicillin acylase in Escherichia coli - Chou, C. P.; Tseng, J. H.; Lin, M. I.; Lin, H. K.; Yu, C. C. (Journal of Biotechnology, 1999)
A strategy of genetically manipulating carbon assimilation with respect to expression of the pac gene was employed for overproduction of recombinant penicillin acylase (PAC). Two expression plasmids of pCLL2902 and pCLL3201, which contain the pac coding region but differ in the pac regulatory region, were constructed for the production experiments. Expression of the pac gene was subjected to phenyl acetic acid (PAA-) induction and glucose catabolite repression for pCLL3201, whereas it was subjected to neither of the two transcriptional regulations for pCLL2902. The specific PAC activity for strains harboring pCLL2902 was significantly higher than that for strains harboring pCLL3201 due to an improved transcription efficiency. In addition, no inclusion bodies were observed upon production of PAC using the current expression systems. The results suggest that using the native pac promoter instead of a strong promoter such as tac for regulation is a feasible approach for production of PAC. The impact of the current expression systems is also significant from a process viewpoint since, using strains harboring pCLL2902, not only could glucose replace PAA as a carbon source of Escherichia coli cultures for production of PAC but also the volumetric PAC activity was highly improved. (C) 1999 Elsevier Science B.V. All rights reserved.